Comparison of experimental and finite element analysis results of a sheet metal prototype vehicle door hinge in X, Y and Z directions - Özgül,Hande Güler (2021)
ABSTRACT In this study, the geometric differences which have a significant effect on the simulation results of the sheet metal prototype vehicle door hinge have been revealed. This geometric difference was examined by finite element simulations and experimental tests for the loads in the X, Y and Z directions specified in the UNECE R11 regulation. As a result, the curves of the finite element simulations and the experimental tests compared for each direction were examined and it was concluded that the compatible model with the experimental tests of the sheet metal prototype vehicle door hinge was 3D scan model.